Atmometer and crop coefficient use in irrigation scheduling in silage corn - Reyes-González, Arturo; Reta-Sánchez, David Guadalupe; Sánchez-Duarte, Juan Isidro; Preciado-Rangel, Pablo; Rodríguez-Moreno, Victor Manuel; Ruiz-Álvarez, Osias (Ecosistemas y Recursos Agropecuarios, 2023)
Irrigation scheduling is a key factor for efficient water management in agriculture. The objective of the study was to program the irrigations withthe use of the atmometer and the crop coefficient (Kc) in forage corn (Zea mays L.) to evaluate its effect on plant height, leaf area index, dry matter yield (DM) andwater use efficiency (WUE) under different irrigation treatments. The study was carried out in the Experimental Field La Laguna of INIFAP located in Matamoros,Coahuila, Mexico. Three corn hybrids (H-431, H-383 and SB-302) were used with a subsurface drip irrigation system, applying 60, 80 and 100% evapotranspiration (ET) treatments and a control (gravity irrigation). The experimental design was completely randomized blocks with divided plots and four replications. Irrigation scheduling with the atmometer and Kc of corn led to a higher DM yield (18.83 t ha−1) and WUE (3.66 kg DM m−3) in the three hybrids with 100% ET. The WUE in 100% ET was 1.36, 1.63 and 40% higher with respect to 60%, 80% ET and irrigation by gravity, respectively. Therefore, scheduling irrigation using the atmometer and crop Kc in a subsurface drip irrigation system helps to obtain more efficient water use in forage corn.